Legitimacy of unseen actors in international adjudication - Baetens, Freya (Studies on international courts and tribunals, 2019)
International courts and tribunals differ in their institutional composition and functions, but a shared characteristic is their reliance on the contribution of individuals other than the judicial decision-makers themselves. Such 'unseen actors' may take the form of registrars and legal officers, but also non-lawyers such as translators and scientific experts. Unseen actors are vital to the functioning of international adjudication, exerting varying levels of influence on judicial processes and outcomes. The opaqueness of their roles, combined with the significance of judicial decisions for the parties involved as well as a wider range of stakeholders, raises questions about unseen actors' impact on the legitimacy of international dispute settlement. This book aims to answer such legitimacy questions and identify 'best practices' through a multifaceted enquiry into common connections and patterns in the institutional composition and daily practice of international courts and tribunals